ลักษณะเฉพาะของอาร์กอนโกลว์ดิสชาร์จพลาสมาผลิตโดยใช้แหล่งไฟฟ้ากระแสสลับความถี่ต่ำ - วัชรพล คงพิบูลย์กิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Properties of plasma argon glow discharge operating with various operating pressure are measured and presented in this work. The argon plasma is produced by a parallel conducting electrodes coupling with high voltage AC power supply. The power supply can generate high AC voltage at various frequencies. The frequencies for the operation are in the range of a few kHz. The system is capable of generating electric field between the two metal electrodes discharge system. The characteristics of the plasma produced are measured by optical emission spectroscopy (OES) technique where electron temperature (kBTe) can be determined by line intensity ratio method and the Boltzmann graph. The value of electron number density (ne) is then determined from Saha-Boltzmann equation. Our results show that the electron number density of the discharge obtained is of the order of 1015 - 1017 m-3 where the electron temperature is between 1.00 - 1.50 eV for triangle signal various operating frequencies between 500 - 8,000 Hz used which are in good agreement with similar results published earlier.